PENTINGNYA PERLINDUNGAN HUKUM PELAKU USAHA MELALUI YAYASAN PERLINDUNGAN HUKUM PELAKU USAHA INDONESIA - Andika Wira Kesuma (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
Legal protection for business actors is felt to be very important, especially in running a business in running their business. The formulation of the problem in this study is 1) What is the role of the Indonesian Business Actor Legal Protection Foundation towards business actors in Indonesia? and 2) What are the obstacles faced in providing legal protection to business actors in Indonesia? The research method used is empirical research. Sources of data used in this study consisted of primary data and secondary data. Business actor is any individual or business entity, whether in the form of a legal entity or not a legal entity established and domiciled or conducting activities within the territory of the Republic of Indonesia, either alone or jointly through agreements to carry out business activities in various fields. The Indonesian Business Actor Legal Protection Foundation (YPH-PUI) is a non-governmental non-profit organization established in Indonesia with a legal domicile in the city of Lubuklinggau on April 20, 2018. The legal protection foundation for Indonesian business actors stands on the side of business actors so that they can get legal justice without any discrimination. between business actors and consumers. The legal protection foundation for Indonesian business actors was established based on the 1945 law article 28 D paragraph 1 which reads: everyone has the right to recognition, guarantees of protection and fair legal certainty and equal treatment before the law and the 1945 law article 28 J paragraph 2: Everyone has the right to be free from discriminatory treatment on any basis and is entitled to protection against discriminatory treatment. Business actors and consumers are symbiotic mutualism because business actors and consumers are mutually beneficial, therefore business actors and consumers must be protected by law. heed the laws and regulations of the Republic of Indonesia and business actors in carrying out their business must obey the law and statutory regulations.According to Setiono, legal protection is an action or effort to protect the public from arbitrary actions by the authorities that are not in accordance with the rule of law, to create order and peace, thus enabling humans to enjoy their dignity as human beings.15 Meanwhile, Satjipto Raharjo stated that legal protection is provide protection for human rights that have been harmed by others and that protection is given to the community so that they can enjoy all the rights granted by law. Because the nature and purpose of law, according to him, is to provide protection (protection) to the community, which must be realized in the form of legal certainty. Legal protection is a preventive and repressive measure. The Indonesian Business Actor Legal Protection Foundation establishes a healthy relationship between business actors and consumers The healthy relationship referred to in this journal is a relationship that does not harm each other, namely business actors and consumers and provides a sense of security and comfort for both business actors and consumers